Effect of a soft wearable robot suit with hip extensor assistance on gait in patients with Parkinson’s disease: a study protocol - Shin, Hyun Iee; Lee, Ho Seok; Yun, Na Young; Choi, Haerin; Lim, Kyeongmin; Lee, Byung Chan; Park, Se Jun; Lee, Ki Ho; Cho, Byeong Jun; Lee, Giuk; Kim, Don-Kyu (Frontiers in Neurology, 2025)
BackgroundParkinson’s disease (PD) is a neurodegenerative disorder characterized by progressive motor deficits and gait disturbances. While medication offers symptomatic relief, long-term complications and gradual functional decline remain significant challenges. Robot-assisted training provides intensive, task-specific motor rehabilitation and has shown promise in improving gait for PD patients. Soft wearable robot suits, designed with lightweight, flexible materials, offer enhanced comfort, adaptability, and biomechanical support compared to traditional robots. However, there is limited evidence regarding the effectiveness of hip extensor assistance with soft wearable robots for gait improvement in PD.MethodsThis is a prospective, single-center, single-blind, parallel-group study, and will recruit 34 PD patients. The participants will be assigned to either a robot or control group. Both groups will receive identical rehabilitation interventions, each session comprising 20-min of strength training, 5-min rest, and 20-min of treadmill walking. The rehabilitation program will be applied identically to all participants. The key difference between the groups will be whether participants wear the soft wearable robot suit during treadmill walking session. The intervention will be conducted 2 times per week, a total of 12 sessions for 6 weeks. The H-Medi (HUROTICS, Inc.), a cable-driven soft wearable robot suit will be utilized for the intervention and hip extensor assistance will be applied. For outcome measures, the following assessments will be performed at baseline (T0) and post-intervention (T1): Gait speed, Timed-Up and Go test, Short Physical Performance Battery, Berg Balance Scale, Movement Disorder Society-Unified Parkinson’s Disease Rating Scale, Freezing of Gait Questionnaire, gait parameters, muscle strength and endurance, quadriceps muscle thickness, body composition, cognition, and depression. The primary outcome will be the difference of gait speed from T0 to T1. The secondary outcomes will be the differences of other measures.DiscussionThis study will be the first to assess hip extensor assistance provided by a soft wearable robot suit as a targeted therapy for gait impairment in PD. Results are expected to clarify device usability, safety, and impact on gait. By focusing on hip extension, the findings may help advance personalized gait rehabilitation and inform the design and clinical adoption of future wearable robotic devices for PD.Clinical trial registrationKCT0010793.